The Flight : A Father's War, a Son's Search - Bridges, Tyler (Book collections on Project MUSE., 2021)
"Intended for general readers and World War II enthusiasts, Tyler Bridges's "The Flight" is part World War II history and part memoir. It is both the story of the harrowing wartime experiences of Bridges's father as well as an account of the journey he made to recover that part of his dad's history. That search led him on an odyssey that stretched into archives in the United States and Europe, and into the memories of his father's comrades and contemporaries. It is also a story about fathers and sons and what can get lost in the gulf between generations as well as how patience and understanding can bridge that gap. Part one of "The Flight" tells the story of Richard W. "Dick" Bridges, an ordinary soldier from Fort Wayne, Indiana, who had an extraordinary war. Dick dropped out of Indiana University immediately after the Japanese attack on Pearl Harbor to enlist in the Army Air Force. For eighteen months, he trained to become a bomber pilot before the Army deployed him to the European Theater. On October 1, 1943, on his ninth mission, Bridges took off from Tunisia at the controls of a B-24 named the Fascinatin' Witch. The target: a factory and airfield in the city of Wiener Neustadt, Austria. It was supposed to be simple, what pilots called a "milk run." Nonetheless, German planes attacked the Witch just after the aircraft dropped its bombs. The strike killed three of its crew members; six others bailed out of the burning plane. Bridges was just about to follow them when the Witch exploded with him aboard. The blast burned him, but he miraculously survived, having deployed his parachute in the chaos. On the ground, bloody and barefooted, Bridges evaded capture. He spent a night in a forest, and at dawn crossed the border into Hungary. After surrendering to Hungarian authorities, Bridges became the first American prisoner of war in that country. Unsure of what to do with him, the Hungarian government stowed him in a country estate that housed Polish internees. Two months later, despite living in comfortable conditions, the young pilot carried out his soldier's oath to escape. Hungarian authorities quickly recaptured him and placed him in a medieval castle. In March 1944, when the Germans invaded Hungary, officials transferred Bridges to a POW camp in Belgrade, Yugoslavia. A month later, American warplanes inadvertently bombed the camp during an attack on the city. Bridges survived, but only narrowly. That night, he and four other prisoners escaped through a hole in the perimeter fence. Three days later, when all hope seemed lost, they were about to surrender when the men came upon Tito's Partisans, who were engaged in a fierce guerrilla war with German forces. The Partisans took in the five men and, by night and under the nose of the Germans, moved them to a hideaway located in small mountain range outside of Belgrade. One day, by pure chance, the five escapees ran into a British officer who had dropped behind enemy lines to assist the Partisans. The officer passed word back to headquarters about the men via wireless telegraph. German forces, however, tried to trap the Partisans in the mountain range. They and the Allied prisoners escaped during an all-night march that skirted German patrols. On July 20, 1944, in the dead of night, a British plane landed on an improvised airstrip surrounded by woods and airlifted them to safety in Italy. Dick Bridges's war was over. Part two of "The Flight" begins with his funeral in 2003 and publication of an obituary in the local newspaper that hailed him as a World War II hero. Curious about that aspect of his father's life-one that he rarely spoke about-Tyler Bridges, the youngest of his seven children, began to reflect upon his ambivalent feelings about his father's quiet and unambitious nature and their often-distant relationship. The younger Bridges decided to piece together the story of his father's war to understand him better. In the process, he connected with the families of the other crew members aboard the Fascinatin' Witch -including that of the Jewish airman who had vowed never to be captured by the Nazis and went down with the airship after saving the life of another crew member. Tyler Bridges also retraced his father's footsteps in Austria, Hungary, and what is now Serbia. He not only uncovered the full extent of his father's story-which he knew almost nothing about-but also gained a deep appreciation of why his dad wanted a quiet life after the war"--